If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x(6x + -4) = 44 Reorder the terms: 11x(-4 + 6x) = 44 (-4 * 11x + 6x * 11x) = 44 (-44x + 66x2) = 44 Solving -44x + 66x2 = 44 Solving for variable 'x'. Reorder the terms: -44 + -44x + 66x2 = 44 + -44 Combine like terms: 44 + -44 = 0 -44 + -44x + 66x2 = 0 Factor out the Greatest Common Factor (GCF), '22'. 22(-2 + -2x + 3x2) = 0 Ignore the factor 22.Subproblem 1
Set the factor '(-2 + -2x + 3x2)' equal to zero and attempt to solve: Simplifying -2 + -2x + 3x2 = 0 Solving -2 + -2x + 3x2 = 0 Begin completing the square. Divide all terms by 3 the coefficient of the squared term: Divide each side by '3'. -0.6666666667 + -0.6666666667x + x2 = 0 Move the constant term to the right: Add '0.6666666667' to each side of the equation. -0.6666666667 + -0.6666666667x + 0.6666666667 + x2 = 0 + 0.6666666667 Reorder the terms: -0.6666666667 + 0.6666666667 + -0.6666666667x + x2 = 0 + 0.6666666667 Combine like terms: -0.6666666667 + 0.6666666667 = 0.0000000000 0.0000000000 + -0.6666666667x + x2 = 0 + 0.6666666667 -0.6666666667x + x2 = 0 + 0.6666666667 Combine like terms: 0 + 0.6666666667 = 0.6666666667 -0.6666666667x + x2 = 0.6666666667 The x term is -0.6666666667x. Take half its coefficient (-0.3333333334). Square it (0.1111111112) and add it to both sides. Add '0.1111111112' to each side of the equation. -0.6666666667x + 0.1111111112 + x2 = 0.6666666667 + 0.1111111112 Reorder the terms: 0.1111111112 + -0.6666666667x + x2 = 0.6666666667 + 0.1111111112 Combine like terms: 0.6666666667 + 0.1111111112 = 0.7777777779 0.1111111112 + -0.6666666667x + x2 = 0.7777777779 Factor a perfect square on the left side: (x + -0.3333333334)(x + -0.3333333334) = 0.7777777779 Calculate the square root of the right side: 0.881917104 Break this problem into two subproblems by setting (x + -0.3333333334) equal to 0.881917104 and -0.881917104.Subproblem 1
x + -0.3333333334 = 0.881917104 Simplifying x + -0.3333333334 = 0.881917104 Reorder the terms: -0.3333333334 + x = 0.881917104 Solving -0.3333333334 + x = 0.881917104 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.3333333334' to each side of the equation. -0.3333333334 + 0.3333333334 + x = 0.881917104 + 0.3333333334 Combine like terms: -0.3333333334 + 0.3333333334 = 0.0000000000 0.0000000000 + x = 0.881917104 + 0.3333333334 x = 0.881917104 + 0.3333333334 Combine like terms: 0.881917104 + 0.3333333334 = 1.2152504374 x = 1.2152504374 Simplifying x = 1.2152504374Subproblem 2
x + -0.3333333334 = -0.881917104 Simplifying x + -0.3333333334 = -0.881917104 Reorder the terms: -0.3333333334 + x = -0.881917104 Solving -0.3333333334 + x = -0.881917104 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.3333333334' to each side of the equation. -0.3333333334 + 0.3333333334 + x = -0.881917104 + 0.3333333334 Combine like terms: -0.3333333334 + 0.3333333334 = 0.0000000000 0.0000000000 + x = -0.881917104 + 0.3333333334 x = -0.881917104 + 0.3333333334 Combine like terms: -0.881917104 + 0.3333333334 = -0.5485837706 x = -0.5485837706 Simplifying x = -0.5485837706Solution
The solution to the problem is based on the solutions from the subproblems. x = {1.2152504374, -0.5485837706}Solution
x = {1.2152504374, -0.5485837706}
| x^2+xy=30 | | x^2-15x-12=0 | | 2n=4+20 | | -(x-1)x-9(x-1)=0 | | -2n+11=5 | | 3n-7=20 | | 8(w-3)=4(3-w) | | X^3-24x=0 | | -2/3t+2-3/4t=-4 | | 2/5x=3/4 | | a^2+50=0 | | q+7-2(q-2)=3(2q+1)+5q | | 1/2x+5+1/3x-5 | | 2a-10=2 | | 13n=42-3 | | 7x+6=9x | | 3x/x-5-5/x-2 | | 13x+195=13(3x+15) | | 4/3z-7+2/3z=-1 | | 88-5x=2x+11 | | -6/x-5-8/x+7 | | 15X+3-7X+4-8X=0 | | 144x^3-258x^2+105x=0 | | pi=3.1416 | | 2x+6/4+5x-2/8 | | 1/2t=-13 | | 7(x-1)=2(2x+4) | | 4x+z=19 | | X+3.5=8.8 | | -x^2-6x+5y^2+10y=22 | | 7(x-5)+14=-7 | | 6x+3=8x-3x |